COVID-19 and Nutrition Implications: A Review - Maioli, Claudio; Cioni, Federico (Progress in Nutrition, 2021)
Coronavirus disease arose in 2019 (COVID-19) and has been defined a current global pandemic by the WHO (Word Health Organization). Several challenges have arisen on how to treat the disease and how to prevent it. A key role for prevention is to optimally support the immune system in the general population so that the immune response is as effective as possible. This depends also on an adequate nutritional intake able to strengthen the defenses against infection. In this review we will review the most important nutrients related to COVID disease defense.